Competition of politicians for wages and office - Hans Gersbach (University of Heidelberg, Department of Economics, 2003)
We examine a model in which two politicians compete for office and for wages. Their remunerations are either set by the public or are offered competitively by the candidates during campaigns. Our main finding shows that competitive wage offers by candidates lead to lower social welfare than remunerations predetermined by the public, since less competent candidates are elected or wage costs are higher.
Keywords: D70; D80; 330; Competitive wage offers; remunerations of politicians; elections; free riding and under provision; incentive contracts; Politiker; Leistungsentgelt; Leistungsanreiz; Lohn; Ökonomische Theorie der Demokratie